2014
DOI: 10.4172/2157-7471.1000236
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Systemic Resistance in Sugar- Beet against Root-Knot Nematode with Commercial Products

Abstract: The potentials of Bio-arc (a commercial formulation of the Bacillus megaterium) at the rate of 5, 10, 15 and 20 ml and Nemastrol (a commercial formulation of active ingredients) at the rate of 0.25 ml, for induction of systemic resistance to sugar-beet var. Negma infected with M. incognita were conducted in two soil types. Results revealed that all treatments with tested rates were found to have nematicidal activity against nematode infection and improved plant growth parameters of sugar-beet with various leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The greatest suppression in nematodes population (95.7%), root galling (83.0%), and number of egg masses (100%) was also sustained at the soil amended with ginger +clove + bio-arc + bio-zed+ oxamyl since incorporation of such organic materials into soil might enhance B. megaterium and Trichoderma album activity that initiates antibiotics towards nematode population. Results of this study support the findings of Mostafa et al (2014) andEl Destiny (2016) in respect of the microbial activity, i.e., B. megaterium in the soil is enhanced on the incorporation of organic matter that initiated antibiosis towards the nematode activity. Padgham and Sikora (2007) reported that B. megaterium caused a repellence of M. graminicola from rice roots.…”
Section: Nematode Alonesupporting
confidence: 89%
“…The greatest suppression in nematodes population (95.7%), root galling (83.0%), and number of egg masses (100%) was also sustained at the soil amended with ginger +clove + bio-arc + bio-zed+ oxamyl since incorporation of such organic materials into soil might enhance B. megaterium and Trichoderma album activity that initiates antibiotics towards nematode population. Results of this study support the findings of Mostafa et al (2014) andEl Destiny (2016) in respect of the microbial activity, i.e., B. megaterium in the soil is enhanced on the incorporation of organic matter that initiated antibiosis towards the nematode activity. Padgham and Sikora (2007) reported that B. megaterium caused a repellence of M. graminicola from rice roots.…”
Section: Nematode Alonesupporting
confidence: 89%
“…Several rhizobacteria can enhance plant resistance against pathogens by activating defense-related enzymes ( Chen et al, 2009 ; Fatma et al, 2014 ; Narendra Babu et al, 2015 ; Salla et al, 2016 ; Rais et al, 2017 ). PAL has been reported to be involved in plant defense mechanisms as it is the first enzyme in phenylpropanoid metabolism and related to the biosynthesis of phenolics and SA ( Jain and Choudhary, 2014 ; Di Lelio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…One such practice is the use of elicitors of plant resistance, which act by activating natural defense responses through different biochemical routes, ultimately inducing systemic resistance in plants (Mostafa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%